2012
DOI: 10.1590/s1806-83242012005000009
|View full text |Cite
|
Sign up to set email alerts
|

Eroded dentin does not jeopardize the bond strength of adhesive restorative materials

Abstract: This in vitro study evaluated the bond strength of adhesive restorative materials to sound and eroded dentin. Thirty-six bovine incisors were embedded in acrylic resin and ground to obtain flat buccal dentin surfaces. Specimens were randomly allocated in 2 groups: sound dentin (immersion in artificial saliva) and eroded dentin (pH cycling model -3× / cola drink for 7 days). Specimens were then reassigned according to restorative material: glass ionomer cement (Ketac TM Molar Easy Mix), resin-modified glass ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
2
20
1
10
Order By: Relevance
“…27,28 Cruz et al 27 evaluated the microshear bond strength in the dentin of bovine teeth and reported KM values around 7.0 Mpa, as also observed in this study. The same results were also verified by Tedesco et al 28 On the other hand, when the bond strength performance of GIC was evaluated by the microtensile bond strength test, higher values were obtained.…”
Section: Discussionsupporting
confidence: 81%
“…27,28 Cruz et al 27 evaluated the microshear bond strength in the dentin of bovine teeth and reported KM values around 7.0 Mpa, as also observed in this study. The same results were also verified by Tedesco et al 28 On the other hand, when the bond strength performance of GIC was evaluated by the microtensile bond strength test, higher values were obtained.…”
Section: Discussionsupporting
confidence: 81%
“…One hundred and eighteen studies were retrieved, but only full papers in English were taken into consideration. In 76 papers, in vitro experiments were performed by using artificial saliva formulations, in which the following formulas were used most often -artificial saliva according to: (1) Klimek et al [1982], which was the first artificial formula introduced for in vitro studies (differences in mucin content) -17 studies [Attin et al, 1998[Attin et al, , 2000Lennon et al, 2006;Wiegand et al, 2006Wiegand et al, , 2007Magalhaes et al, 2008a;Wiegand et al, 2008aWiegand et al, , 2009aSouza et al, 2010;Wegehaupt and Attin, 2010;Yu et al, 2010a;Levy et al, 2011;Rochel et al, 2011;Magalhaes et al, 2011;Comar et al, 2012;Magalhaes et al, 2012]; (2) Vieira et al [2005] -17 studies [Kato et al, 2007;Magalhaes et al, 2007;Francisconi et al, 2008;Magalhaes et al, 2008b;Kato et al, 2009;Magalhaes et al, 2009;Rios et al, 2009;Bueno et al, 2010;Kato et al, 2010;Magalhaes et al, 2010a, b;Moretto et al, 2010;Barbosa et al, 2011;De Carvalho Filho et al, 2011;Manarelli et al, 2011;Barbosa et al, 2012;Cruz et al, 2012]; (3) Amaechi et al [1998b] -13 studies [Amaechi et al, 1998a…”
mentioning
confidence: 99%
“…The reduction of dentin bond strength is widely reported 20,21 and it is probably a consequence of the combination of these deleterious effects. Only one study reported that eroded dentin does not jeopardize the immediate microtensile bond strength of the adhesive restorative materials evaluated 22 . This result might be related to the different pH cycling mode, products and test utilized in the contradictory study.…”
Section: Discussionmentioning
confidence: 99%
“…It infers a good reliability of the present µTBS test conditions and correlates well with the literature for eroded dentin bonded to adhesive systems 20,[30][31][32] . On the other hand, eroded dentin restored with ionomer based materials usually shows higher incidence of cohesive and mixed failure 22 . This fact might be related to the intrinsic cohesive material properties and also associated to the very common presence of air bubbles in glass ionomer cements that can act as stress points, increasing the likelihood of cohesive fracture within the cement 33 .…”
Section: Discussionmentioning
confidence: 99%